Neuronal Tissue-Nonspecific Alkaline Phosphatase (TNAP) - Fonta, Caroline.; Fonta, Caroline.; Négyessy, László.; Négyessy, László. (Subcellular Biochemistry,, 2015)
Phosphatases such as TNAP are fundamental in regulating cellular, and consequently numerous body functions. TNAP is a ubiquitous enzyme with a wide spectrum of substrates and specificity regulation at the cellular level and the lack of TNAP activity is a lethal condition. Recent findings of a highly specific regional, laminar and subcellular localization of TNAP in the cerebral cortex indicates that in addition to its metabolic and skeletal functions, TNAP also plays a role in regulating cerebral functions, most probably cognition. In fact, TNAP disturbance could result in complex diseases such as epilepsy, developmental retardation and Alzheimer disease. Available data suggest that, regarding brain functions, TNAP is a potentially important target of clinical research. The proposed book aims to provide an overview of our current understanding of the functions of TNAP in the brain.